Nonproliferative and proliferative retinopathy - Salam, Adzura (2019)
Diabetic retinopathy falls into two main classes: non proliferative and proliferative. The word "proliferative" refers to whether or not there is neovascularization (abnormal blood vessel growth) in the retina. Non-proliferative diabetic retinopathy, previously called background retinopathy, is the earliest stage of  diabetic  eye disease. Non-proliferative diabetic retinopathy is initially characterised by microaneurysms (microscopic blood-filled bulges in the artery walls) which may burst and leak into the retina. Tiny spots or dots of blood may accumulate in the retina, but they usually do not produce noticeable symptoms in the early stages of the disease. As the disease progresses,  hard exudates  (accumulations of fluid that has leaked from blood vessels), abnormalities in the growth of microscopic blood vessels in the retina, and bleeding from the veins that feed the retina may occur. Non-proliferative disease progresses from mild to moderate to severe. While non-proliferative diabetic retinopathy is not itself a sight-threatening condition, it can trigger macular oedema or macular ischaemia, which are other forms of diabetic retinopathy that may cause rapid vision loss at any stage of non-proliferative disease. In addition, the vascular changes that occur in non-proliferative retinopathy lead to retinal ischaemia (lack of blood flow to the retina) and trigger progression to sight-threatening proliferative disease. As the severity of non-proliferative retinopathy increases, the risk of developing sight-threatening proliferative diabetic retinopathy also increases. Proliferative diabetic retinopathy is characterised by  neovascularisation  – that is, the growth of abnormal new blood vessels in the retina. The vessels are weak and may burst and bleed into the retina or  vitreous fluid  (fluid surrounding the retina), causing vision loss.